A Neanderthal's specialised burning structure compatible with tar obtention - Juan Ochando; Francisco J. Jiménez-Espejo; Francisco Giles-Guzmán; Carlos Neto de Carvalho; Jose S. Carrión; Fernando Muñiz; Juan Manuel Rubiales; Pedro Cura; João Belo; Stewart Finlayson; Belen Martrat; Barend L. van Drooge; et al. (Quaternary Science Reviews, 2024)

Ancient DNA: a promising tool for understanding the evolutionary history of and human pressure on the highly endangered limpet Patella ferruginea - Free Espinosa; James Haile; Stewart Finlayson; Francisco Giles-Guzman; Geraldine Finlayson; Clive Finlayson; Darren A. Fa (Conservation Genetics Resources, 2024)

A comparative study of the in vitro dermal absorption of radiolabeled benzophenone through human skin - Sadaff Ejaz; Clive Roper; Zoe Finlayson; Kyle S. Saitta; Timothy McCarthy; Frank Sun; Michael D. Southall (Toxicology in Vitro, 2024)

Close encounters vs. missed connections? A critical review of the evidence for Late Pleistocene hominin interactions in western Eurasia - Clive Finlayson; Christoph Zollikofer; Marcia Ponce de León; Geraldine Finlayson; José Carrión; Stewart Finlayson; Francisco Giles Guzmán; John Shea (Quaternary Science Reviews, 2023)

Neanderthal footprints in the “Matalascañas trampled surface” (SW Spain): new OSL dating and Mousterian lithic industry - Carlos Neto de Carvalho; Fernando Muñiz; Luis M. Cáceres; Joaquín Rodríguez-Vidal; Alicia Medialdea; Miren del Val; Pedro Proença Cunha; Jose María García; Francisco Giles-Guzmán; José S. Carrión; Zain Belaústegui; Antonio Toscano; et al. (Quaternary Science Reviews, 2023)

Coastal raptors and raiders: New bird tracks in the Pleistocene of SW iberian Peninsula - Carlos Neto de Carvalho; João Belo; Silvério Figueiredo; Pedro P. Cunha; Fernando Muñiz; Zain Belaústegui; Mário Cachão; Joaquín Rodriguez-Vidal; Luis M. Cáceres; Andrea Baucon; Andrew S. Murray; Jan-Pieter Buylaert; et al. (Quaternary Science Reviews, 2023)

Iberian Neanderthals in forests and savannahs - Juan Ochando; Gabriela Amorós; José S. Carrión; Santiago Fernández; Manuel Munuera; Jon Camuera; Gonzalo Jiménez‐Moreno; Penélope González‐Sampériz; Francesc Burjachs; Ana B. Marín‐Arroyo; Mirjana Roksandic; Clive Finlayson (Journal of Quaternary Science, 2022)
This article aims to delve into the reality of glacial refuges of forests and tree species (including conifers, mesothermophilous angiosperms and xerothermic scrub) during the cold dry phases of the Iberian Pleistocene in which there is evidence of occupation of Middle Palaeolithic people. The research framework focuses on the eastern sector of the Iberian Peninsula due to the physiographic, palaeobotanical and archaeological peculiarities, substantiated by recent studies. We contend that some Neanderthal occupations developed in the context of high geobiological complexity, high biological diversity and highly structured forest ecosystems. We highlight the importance of glacial refuges as local anomalies that, however, would be contingent on vegetational development, and on the survival of Palaeolithic groups in areas with a broad diversity of natural resources.

Sea, sickness and cautionary tales: a multi-isotope study from a post-mediaeval hospital at the city-port of Gibraltar (AD 1462–1704) - Emma Lightfoot; Emma Pomeroy; Jennifer Grant; Tamsin C. O’Connell; Petrus le Roux; Sonia Zakrzewski; Sarah Inskip; Sam Benady; Clive Finlayson; Geraldine Finlayson; Kevin Lane (Archaeological and Anthropological Sciences, 2020)
During the sixteenth to eighteenth centuries, Spanish ships sailed around the globe connecting Spain to its colonies. While documentary records offer rich details concerning life on board ship, archaeological information is essential to generating a full picture of the past. The cemetery at Old St Bernard’s Hospital, Gibraltar, provides an opportunity to study the skeletal remains of sailors. Following previous osteological research, carbon, nitrogen, oxygen and strontium isotope analyses were undertaken on thirty-three of these individuals. The results show that the, largely male, individuals had various different diets during life and came from several different places. Diets were largely based on C 3 food chains; some individuals consumed C 3 foods with low δ 13 C values; others consumed some marine foods, and a few individuals had a high trophic level diet, through the consumption of either freshwater resources or a high proportion of animal protein. The individuals spent their childhoods in several different places, although these homelands do not correlate simply with dietary variation. This variety in diets and homelands is consistent with our expectations for this hospital site given its location in a post-mediaeval entrepôt. The interpretation of these results are greatly helped by the available historical information and this has broader implications for the interpretation of isotope data elsewhere where the historical context of the site and the mobility patterns of the individuals are less well known.